The potential and benefits of repurposing existing drugs to treat rare muscular dystrophies. (3rd April 2018) - Ismail, Hesham M.; Dorchies, Olivier M.; Scapozza, Leonardo
ABSTRACT: Introduction : Muscular dystrophies encompass a heterogeneous group of rare genetic neuromuscular disorders affecting locomotor, cardiac and respiratory muscles. These diseases are mostly debilitating progressive disorders with poor prognosis. Despite the discovery of the genetic causes and in depth understanding of the pathophysiological changes that take place in these disorders, efficacious therapies are still to be developed. The expected price of innovative therapies that are reaching the market for such rare disorders are of concern. Areas covered : For this review, Duchenne muscular dystrophy is used as an example of these disorders. Clinical features, pathophysiological processes, socioeconomic impact, investigational and recently marketed therapeutic modalities for this disease and their price tag are discussed. Tools to circumvent cost and time for therapeutic development for such disorders are described highlighting the potential of this pathway and the obstacles to overcome. Expert opinion : Repurposing already existing drugs with a well-studied pharmacokinetic, pharmacodynamic and safety profile holds a tremendous promise in delivering efficacious therapies in a cost controlled and timely manner to patients suffering life-threatening diseases who cannot wait for a classical drug development cycle. The use of this path is accelerated by incentives, guidance and protection provided by holding an orphan drug designation status.